THE PROBLEM OF IMPROPER NUTRITION AMONG YOUTH AND ITS IMPACT ON ACADEMIC PERFORMANCE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This scientific article provides an in-depth analysis of the development of improper eating habits among contemporary youth, particularly students, and its adverse effects on their health and academic performance. The research was carried out based on an experiment conducted among 100 students aged 18–22 who are studying at higher education institutions in Tashkent. Students were divided into two groups based on their eating habits, daily routine, and health status: those with healthy eating habits and those with improper eating habits.